Drivers and barriers to career entry and retention of nurses with initial higher education: A scoping review - Müller, Julia; Breitinger, Florian; Bräuer, Patricia; Dauer, Bettina; Zilezinski, Max; Paulicke, Denny; Jahn, Patrick (GMS Journal for Medical Education, 2025)
Background: While previous systematic reviews have examined specific aspects of the career trajectories of bachelor-qualified nurses, including adjustment strategies, workplace challenges, and support programmes, no comprehensive synthesis exists addressing how these factors interact across the broader early career pathway. This article examines the drivers and barriers influencing entry, role transition, and retention of graduate nurses, providing insights that complement existing research. Methods: A systematic literature search following the principles of a scoping review was conducted in the professional databases MEDLINE via PubMed and CINAHL via EBSCO in February and May 2022, as well as in August 2024. The characteristics of the included studies were summarised narratively in a pre-consented data extraction table. The synthesis of information was performed inductively and organised into three emergent themes: Career Entry, Role Development, and Retention. Results: 31 publications from 13 countries were included in the synthesis and presentation of results. Among these, 18 studies examined factors inhibiting career entry, 10 studies explored role transition, and 3 studies investigated factors influencing retention. Barriers included insufficient team support, fear of making mistakes, and increased workload. Facilitators included support structures, such as mentors and peer networks, as well as designated transition periods. Conclusion: To promote the academic professionalisation of nursing in Germany and integrate of bachelor-qualified nurses into practice, structural frameworks embedded within the nursing process and oriented across multiple levels are essential. These frameworks should address both the barriers and facilitators identified in this review.